Design Aspects of Positional Mooring System Based on LR FOIFL Rules - Ika Prasetyawan; Navik Puryantini (Badan Riset dan Inovasi Nasional, 2012)
Floating offshore units, such as FPSOs, are subject to dynamic excitations from the environment and require to be moored to maintain position at the fix location of operation. In designing positional mooring systems for floating offshore units, systematic analyses must be performed to predict tension levels in the mooring lines and offsets of the floating unit under extreme and ambient service conditions, in order to ensure the mooring arrangement provides a level of safety acceptable to the industry. In order to derive environmental loads pertinent to the location of operation, environmental data should be made available comprising of long and short term current, wind and wave characteristic data specific to the site of operation. Based on LR FOIFL Rules, the performance of positional mooring systems is assessed on the basis of sets of site specific extreme and ambient (or fatigue) environmental conditions. Class rules require consideration of extreme conditions with recurrence period of 100 years (e.g. combination of 100 year waves + 100 year wind + 10 year current).In the process of designing positional mooring systems of FPSOs, designers may start from quasi-static analysis at preliminary design stage, and then investigate various combinations of extreme conditions in the dynamic analysis for a more rigorous approach during the final design stage.The outcomes of the analyses have to be compared against industry standards such as the LR FOIFL rules to confirm the positional mooring systemâ€™s design meets levels of safety recognised as acceptable to the industry. In this paper, an introduction to positional mooring systems for FPSOs, considering typical strength aspects is given, followed by a general description of hydrodynamic characteristics of ship shape FPSOs The design aspects of mooring system is then given in section outlining methodology in mooring analysis using either quasi-static or dynamic method.Â